Pengaruh Citra Merek terhadap Keputusan Pembelian - Nuryanti, Nuryanti; Fawazi, M. Halim; Basuki, Hery; Wati, Juanda Angkasa (STKIP PGRI SITUBONDO, 2024)
Indonesian people have a habit of snacking. This habit opens up business opportunities to produce contemporary food that can be used as a snack between main meals. One food that is familiar to Indonesian people is peanut brittle. However, the current economy is increasingly showing a very rapid pace of competition. So researchers are interested in taking the title The Influence of Brand Image on Purchasing Decisions (Case Study of Peyek Mak Nyus Jingglong Sutojayan Blitar Consumers). The research method used is a quantitative method using a survey method. Meanwhile, the data collection technique is by literature study and questionnaires. The population in this research is Peyek Mak Nyus consumers who have purchased in 2022. Data was obtained from consumer records. The sample used was 49 respondents. Sampling was carried out using saturated samples. From the results of data analysis, it can be seen that the t test value is 0.000, which shows that there is an influence of brand image on purchasing decisions for Peyek Mak Nyus Jingglong consumers, Blitar Regency.